2010
DOI: 10.1002/sia.3309
|View full text |Cite
|
Sign up to set email alerts
|

Improved bonding strength between TiO2 film and Ti substrate by microarc oxidation

Abstract: Titanium (Ti) and its alloys have proved to be very suitable materials for load-bearing bioimplant applications. Unfortunately, Ti and its alloys exhibit poor osteoinductive properties like most metals. This drawback was recently addressed by modified titania (TiO 2 ). However, the bonding strength between TiO 2 and substrate is not very strong. Therefore, mechanical properties and biochemical stability are very important.Many techniques have been investigated for modifying the TiO 2 layer. Microarc oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Modifications haves been performed to minimize the undesired effects. These treatments improve the biocompatibility and increase the strength, Young's Modulus (~100GPa), yield strength (~650 MPa) and corrosion resistance [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Modifications haves been performed to minimize the undesired effects. These treatments improve the biocompatibility and increase the strength, Young's Modulus (~100GPa), yield strength (~650 MPa) and corrosion resistance [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, when titanium is implanted into the living body, encapsulation phenomena always appear on the bone‐implant interface. This complication results both from biological inertness of the implant and the generation of fibrous tissue that causes micro‐movement between the bone and the interface and leads to premature loosening . Therefore, it is crucial to ensure good osseointegration by subjecting the implant to surface modification, otherwise, adequate osseointegration may not be achieved until healing has progressed over a period of months .…”
Section: Introductionmentioning
confidence: 99%
“…Nakagawa et al reported that Mg‐modified pure titanium prepared by a hydrothermal method in MgCl 2 solution demonstrated improved protein adsorption, cell attachment, and spreading. [1b] However, to the best of our knowledge, there are no reports yet describing the effect of the sole incorporation of Mg 2+ on the osteogenic differentiation of stem cells without the existence of Ca 2+ in the titanium.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that previous studies [28][29][30] on the bonding strength of biomaterials were mainly experimental, having a "descriptive" goal, and they concluded that, in general, the bonding strength was weak. On the contrary, the present model and method could quantitatively improve our ability not only in measuring but also in "designing" the bonding strength of biomaterials, making them more suitable for clinic applications in bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%